The Need For Marine Medicine Specialists for An Integrated Service Network Towards Advanced Indonesia 2045 - BOY SUBIROSA SABARGUNA; HARMIN SARANA; KEES DE ROODE; DJATIWIDODO EDI PRATIKNYA; RISMA (Hang Tuah Medical Journal, 2024)
Need for Marine Medicine Specialist Doctors: I. Hospital-Based Study Program, starting to run in 8 study programs, July 2024. II. Service Needs: 1) Regulations, 2) Development of Remote and Coastal Areas, 3) The existence of a Sea Highway, 4) The existence of marine tourism, 5) Fisheries, 6) Defense, 7) The existence of a New National Capital. III. Service Network: 1) Marine Medicine Service Center in the National Capital, 2) Frontline Areas, 3) Coastal Areas, 4) Hospital Ships. IV. Integrated Systems Network: 1) Defense System, 2) Transportation System, 3) Tourism System, 4) Fisheries System, 5) Telemedicine System, 6) Coastal Area Development, 7) Education, Research, Community Service and Innovation Systems. On August 25, 2023, the Marine Medicine Study Program was approved for a SCOR of 0.001/1,000 population, including efforts to accelerate the achievement of meeting needs. Calculation of Minimum Needs: calculated as 50% of the optimal value, 50% x 319 = 159.5 Rounded to 160, UNRAM and UHT Production Three more years: 3 +5 = 8, then it will only be achieved 20 to 40 years later. Proposed Solutions: 1) PRODI at UNRAM and UHT; There are 2 PRODIs with 3 classes: Regular, Parallel, and Scholarship, projected graduates 9+15 =24; 2) Immediately establish 10 Hospital Based PRODIs, this will meet the increasing needs, so produce 10 PRODIs, projected graduates 10 x 10 = 100; 3) Immediately form a Service Network and System Network, spread throughout Indonesia. 9 types, so there are 9 PRODI. Projection of graduates 9 x 10 = 90. Total projection: 24 + 100 + 90 = 214 per semester. Keywords: need for specialist doctors, study program, student class, graduate projections.